Adverse Childhood Experiences, Mindfulness, and Grit in College Students in China - Cheung, Shannon P.; Tu, Bin; Huang, Chienchung (Frontiers in Psychology, 2022)
This study investigated the effect of ACEs and COVID-19 on grit and whether this effect is mediated by mindfulness. Although current scholarship has found that adverse childhood experiences (ACEs) have harmful consequences to individuals across the life span, less is known about the relationship between ACEs and grit. Grit is predictive of educational success and subjective wellbeing. A cross-sectional online survey administered to junior and senior students from 12 universities spread across China was conducted from September 20, 2020 to October 5, 2020. The universities were selected from geographically diverse regions of China to ensure a diverse sample. We received 1,871 completed responses from 2,229 invited students. The survey response rate was 83.9%. The results indicated that ACEs had significantly negative effects on grit, while mindfulness had significantly positive effects on grit. Once controlling for level of mindfulness, the effects of ACEs on grit largely reduced and became insignificant. The findings of this research indicate that mindfulness has a significant mediational effect on the relation between ACEs and grit and call for mindfulness-based interventions for enhancing grit for the population at risks.